Language policy in the Kingdom of Prussia at the junction of the 18th-19th centuries - Aleknavičienė, Ona (Taikomoji kalbotyra, 2021)
The present paper examines the principles of the language policy designed in the Kingdom of Prussia at the junction of the 18th-19th centuries. This research aims to identify the main factors affecting the introduction of the Lithuanian language as the official regional language in the Kingdom of Prussia and to evaluate the parameters applied to such language planning. The main research objects in this study are the prefaces to Christian Gottlieb Mielcke’s dictionary Littauisch-deutsches und Deutsch-littauisches Wörter-Buch (1800) and the archival material of the end of the 18th century, which provide information on the preconditions, directions, goals, and objectives of the language policy of the time. The politics favorable to the Lithuanian language was preconditioned by the political changes in the 18th century. After the third partition of the Commonwealth of the Two Nations (1795) and with the annexation of Užnemunė to Prussia, the range of the Lithuanian language use expanded, and the ideas of regional particularism strengthened. Christoph Friedrich Heilsberg, the author of the third preface to Mielcke’s dictionary, a counsellor in the Königsberg Chamber of War and Domains, and an inspector of East Prussian schools, was well aware of the Lithuanian attitudes to the influence of language on identity, motives for language learning, legislation, and the potential of schools and churches. On the grounds of this versatile expertise, he undertook language status planning. With regards to Mielcke’s observation about civil servants who need to learn Lithuanian and the Lithuanian approach to language, Heilsberg took a practical position on language planning. He suggested expanding the Lithuanian language use in the public sphere rather than considering the idea of German as a common state language. At Heilsberg’s initiative, the Lithuanian language had to be used in such important areas as education, church, law, business, and administration. Heilsberg sought to ensure that it did not lose its cultural or administrative functions. Such plans presuppose the status of Lithuanian as an official regional language, equivalent to linguistic autonomy, where the language of a national minority has political autonomy and coexists with the official language of the state. Heilsberg initiated not only the development but also the implementation of language policy. He developed the directions and measures of corpus planning: to help non-Lithuanians to learn Lithuanian, he encouraged Mielcke to prepare a Lithuanian-German and German-Lithuanian dictionary and supervised the publication of a Lithuanian grammar and a collection of sermons. This highlights the priorities of his education policy, which aimed to develop the language skills of teachers and priests, and to create conditions for civil servants working in the province to learn the Lithuanian language. Three statements of Heilsberg as a high-ranking state official were important for increasing the prestige of the Lithuanian language: 1) language is a guarantor of identity; 2) provincial languages must be learned by civil servants and not vice versa; and 3) language must be nurtured. The author of the fourth preface to Mielcke’s dictionary, the German philosopher Immanuel Kant, raised the criterion of language purity. Considering that only pure language is important for the maintenance of the nation’s distinctiveness, for science, and especially history, he emphasized the need to preserve the purity of language and proposed two ways to achieve this: to use pure language in schools and churches, and to expand the domains of its use. This is the earliest attempt in the history of Prussian Lithuanian culture to give the Lithuanian language the status of an official regional language. Such policy ensured its functioning in all spheres of public life, its use in the education system, and created conditions for maintaining identity.